Transitions: Living With Young‐Onset Alzheimer's Disease: A Qualitative Interview Study - Malin Aspö; Leonie N. C. Visser; Miia Kivipelto; Anne‐Marie Boström; Berit Seiger Cronfalk (Wiley, 2024)
ABSTRACT Introduction Persons with young‐onset dementia (YOD) are confronted with specific challenges. Due to the neurodegenerative nature of the disease, people diagnosed with YOD face many changes with different consequences, for example, regarding their life perspective. These changes can give rise to transition processes and strategies for coping, hopefully stimulating well‐being and acceptance. However, this might not always be the case, and support may be warranted. Our aim was to describe the experiences of those living with YOD due to Alzheimer's disease (AD) and identify signs of transitions during the first year after diagnosis. Method In this qualitative interview study, we explore the experiences of younger persons living with AD. Thirteen participants under the age of 65 years (nine female and four male; mean age: 57) were included 1 year after being diagnosed with AD. The interviews were transcribed verbatim and analyzed using qualitative content analysis with a deductive approach. To gain a deeper understanding of the data, Meleis's transitions theory was used as a theoretical framework. Results Two categories were identified: 'Life has changed' and 'Mastering a changed life situation'. One year after diagnosis, participants described how they experienced a changed life situation, changing symptoms, a loss of meaningful activities and an increased risk of social isolation. Furthermore, living with uncertainty about the future caused feelings of being disconnected. Awareness was described as an important aspect of coping with YOD and progressing in the transition process. Participants also highlighted the importance of support from others. Conclusion The results suggest that preventing social isolation is important in facilitating healthy transitions. Therefore, professionals need to identify signs of transitions and be aware of the complexity of coping with YOD, thereby helping to prevent unwanted responses to change and facilitate a healthy transition process. Patient or Public Contribution The findings are based on interviews with 13 persons with YOD and provide insight into experiences of living with YOD.